Effects Of Accelerated Weathering On The Properties Of Polylactic Acid Toughened With An Ethylene Copolymer As An Impact Modifier - Phommachanh, Kouth (2013)
Polylactic acid (PLA) was melt-blended with different amounts (0 to 30 wt%) of a commercially available ethylene copolymer impact modifier. PLA/ethylene copolymer blends were prepared via a single-screw extruder and compression moulded into test specimens. Accelerated weathering which involved UV exposure was carried out on the blends following ASTM D 154. Changes in the mechanical, thermal properties and morphology were determined after 250, 500, 750, and 1000 hrs of exposure. The mechanical properties of PLA/ethylene copolymer blends were studied through tensile, flexural, fracture toughness and impact test. SEM was used to investigate the morphology of the tensile and impact fracture surfaces as well as the surface morphology of PLA and PLA/ethylene copolymer blends after the UV exposure. The thermal properties were determined using DSC and TGA to investigate the thermal behaviour of PLA and PLA/ethylene copolymer blends before and after the UV exposure. The exposed surface was examined using FTIR and SEM while GPC was used to investigate the molecular weight of neat PLA before and after the UV exposure. The addition of ethylene copolymer showed significant increased in the elongation at break and impact resistance of PLA. This is due to the toughening effect of ethylene copolymer. The addition of 20 wt% ethylene copolymer decreased the tensile strength and tensile modulus by 51.2 and 41.2% respectively. At the same impact modifier content, the flexural strength and flexural modulus decreased by 39.6 and 37.3% respectively. Impact strength of the blend however, increased by 125%. Addition of impact modifier decreased the degree of crystallinity of PLA. Tensile, flexural and impact properties of PLA/ethylene copolymer blends decreased after the accelerated weathering due to the photo-degradation of PLA under the UV exposure as well as hydrolytic degradation of PLA due to the presence of the moisture during the weathering condition. Decreased in the mechanical properties was due to molecular weight degradation of PLA. This was confirmed by the GPC analysis. The samples too exhibited dimensional instability, became brittle and turned slightly yellow after the exposure.